Prevalence of Physical Abuse Among Adolescent with Hearing Impairment (Journal of Asian Development Studies, 2024)
The current study was conducted to explore the level of physical abuse faced by adolescents with hearing impairment. A correlation research design was used. The population for this study comprised the students of (grades 5th-10th) age range (12-18) studying in special education schools and centers of the Gujranwala division. A sample of 350 adolescents with hearing impairment (male 186, female 164) was selected using stratified random sampling for this study. ICAST-1 scale was developed by ISPCAN (2015) for physical abuse and was used for data collection 19 items were selected for physical abuse and validated their content validity by experts. The scale was translated into Urdu and validated by the Urdu language experts. Data was analyzed by reporting frequencies and levels of physical abuse. The findings of this study indicate that almost 90% of the adolescents with hearing impairment were facing moderate levels of physical abuse. The majority face moderate physical abuse in the form of being put in time out, shaken aggressively, pinched to cause pain, locked up or restricted movement, kicking, crushed fingers, and threats with a knife/to hurt or kill you as punishment. We need to reconsider the myth of using punishment to improve children's learning and behavior.